Lifewide or School-Only Learning: Approaches to Addressing the Developing World's Learning Crisis. (April 2019) - Friedlander, Elliott W.; Arshan, Nicole; Zhou, Sen; Goldenberg, Claude
This cluster randomized controlled trial tested the impact of school-only and lifewide-learning (LWL) approaches to supporting early-grade learning over 2 years in rural Rwanda. We compare school-only and LWL treatments with a business-as-usual control condition and with each other. Schools in both treatment groups received reading materials and teacher training. LWL villages also received support to enrich home and community literacy ecologies. Student reading assessments, administered across 21 sectors (analogous to U.S. school districts), showed that both treatments positively impacted learning. LWL produced a greater impact, particularly in oral comprehension, reading fluency, and reading comprehension. However, nearly one third of the students lacked basic skills at endline, indicating that further efforts are needed to address the learning crisis in the least-developed countries.